Dukungan Orang Tua dan Motivasi Berprestasi Anak Usia Muda dalam Olahraga: Sebuah Studi Korelasi dalam Cabang Olahraga Renang - Fadluoh, Firmansyah Mujahid; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Institut Teknologi Bandung, 2024)
Parental support in the development of achievement is one of the crucial factors, especially for young children, as it can influence the development of their skills to achieve high performance. Parental involvement in supporting their child's achievement impacts various aspects, such as motivation, which is generally considered to involve the initiation, direction, intensity, and persistence of individual behavior, and also positively affects the child's confidence and independence in training. This study aims to examine the relationship between parental support and achievement motivation in young children in the sport of swimming. This research employs a quantitative descriptive method with a correlational research design. The population in this study consists of 17 swimming athletes from Delta Valley Cimahi, all of whom were included as the research sample. The research instrument used two questionnaires, each consisting of 36 items regarding parental support and 30 items regarding achievement motivation, completed by the athletes via Google Forms using a Likert scale as the response option. The data was processed and analyzed using the Spearman rank correlation test in SPSS Version 25. The results showed that parental support has a significant correlation with achievement motivation in young children in the sport of swimming. Therefore, it can be concluded that good parental support will lead to higher achievement motivation in young children in the sport of swimming.